2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8857242
|View full text |Cite
|
Sign up to set email alerts
|

Fast Approximate Time-Delay Estimation in Ultrasound Elastography Using Principal Component Analysis

Abstract: Time delay estimation (TDE) is a critical and challenging step in all ultrasound elastography methods. A growing number of TDE techniques require an approximate but robust and fast method to initialize solving for TDE. Herein, we present a fast method for calculating an approximate TDE between two radio frequency (RF) frames of ultrasound. Although this approximate TDE can be useful for several algorithms, we focus on GLobal Ultrasound Elastography (GLUE), which currently relies on Dynamic Programming (DP) to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…We set p = 5 RF lines as trials showed us that choosing a value for p more than 5 would not improve the quality of the strain image [12]. The number of hidden units in the MLP classifier is a hyperparameter that is chosen in a way so as to have the highest accuracy on the validation data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We set p = 5 RF lines as trials showed us that choosing a value for p more than 5 would not improve the quality of the strain image [12]. The number of hidden units in the MLP classifier is a hyperparameter that is chosen in a way so as to have the highest accuracy on the validation data.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that steps 2 and 3 in Algorithm 1 are very computationally complex. As such, they cannot be performed in real-time for selecting optimal pairs of RF RF frames I 1 and I 2 are passed to PCA-GLUE [16], [17] to obtain the displacement image.…”
Section: A Data Collectionmentioning
confidence: 99%
“…3) PCA-GLUE, which relies on DP to compute the initial displacement map, is robust to potential DP failures. This work is an extension of our recent work [39], [40], with the following major changes. First, we replace the multi-layer perceptron (MLP) classifier with a more robust one that can generalize better to unseen data.…”
mentioning
confidence: 93%
“…In addition, to avoid the over-smoothing induced by the quadratic regularization function used in GLUE and GUEST, total variation regularization has been proposed in [57]. Furthermore, principal components of the displacement field have been investigated in [58], [59] to reduce the execution time of GLUE. In [60], multi-scale pyramidal approach has been adopted to refine the DP integer estimate.…”
Section: Introductionmentioning
confidence: 99%